PENGARUH REKRUTMEN DAN PELATIHAN TERHADAP KINERJA FRONTLINER BRI (BANK RAKYAT INDONESIA) CABANG SIBOLGA - DINA SARAH SYAHREZA; DITHA IVANY TAMBUNAN (LP2MTBM MAKARIOZ, 2023)
This study aims to determine the effect of Recruitment and Training on BRI (Bank Rakyat Indonesia) Sibolga Branch Frontliner Performance using quantitative methods. The sampling technique used used saturated samples, with a total sample size of 40 respondents. The instrument used in this research was carried out by distributing questionnaires and statistically processed using multiple linear regression analysis to test the research hypotheses. The results showed that partially Recruitment has a significant effect on BRI (Bank Rakyat Indonesia) Frontliner Performance, as well as Training partially has a significant effect on BRI (Bank Rakyat Indonesia) Frontliner Performance. Furthermore, the results of the F test also show that simultaneously Recruitment and Training also have a significant effect on the performance of BRI Frontliners (Bank Rakyat Indonesia).The ability of the model to explain the behavior of BRI Frontliner Performance (Bank Rakyat Indonesia). Sibolga which is shown by the coefficient of determination shows a value of 27.2% while the rest is influenced by other variables outside this study.